A web-based baby names selection system report (babysport) / Erin Andreana Jacob - Erin Andreana, Jacob (2002)
Getting the right thesis topic these days can be really difficult. Everyone wants to develop a system that is the most latest, popular, and most important of all different from the other seniors, but at the same time simple and not too complex. In line with this, I wanted to do something different from the others. Names have deeper meaning than meets the eyes. English names, for an example originate from Greek, Hebrew French and etc. Indian names on the other hand come from different ethnic group such as Jain, Hindu, Sikh, Tamil and so on. We may not realize it but each name holds a different meaning and says a lot about the person who carries it. I have developed a web-based system that is able to provide meaning and origins of either an English Malay, Chinese or Indian name. The system I designed is basically an online guide for would-to-be parents in choosing a name for their baby. It is called 'Baby Spot". It will be accessible on the Internet. In this modem world, everything and anything is possible on the Internet, even baby names. Although it is targeted to parents, users interested in knowing the meaning and origins of their name are welcomed to visit the web site.